Constructing a digital shield: A systematic review of mobile learning interventions for cyberbullying prevention towards primary school education - Zulkafli, Syamsol Azhar; Mohamad, Mariam; Saibon, Jamalsafri; Saibon, Ramdzan Ali (Journal of Islamic, Social, Economics and Development, 2026)
Purpose: This study addresses a critical gap in the educational body of knowledge concerning the prevention of cyberbullying among the primary school students (aged 9-12). While the traditional bullying has been extensively studied, the increasing exposure of younger children to the online aggression has outpaced the development of the effective pedagogical interventions. Methodology: guided by Park’s Pedagogical Framework for Mobile Learning, this study employs a conceptual analysis to examine the effectiveness of the gamified mobile learning applications in enhancing students’ digital safety knowledge. Selected interventions, including Google Interland and Common Sense Media’s Digital Passport, were analysed in terms of pedagogical structure, learner engagement, and social interaction. Findings: The analysis reveals that while current applications effectively support structured knowledge and digital citizenship awareness, their high transactional distance and individualized design offer limited avenues for collaborative reflection and interpersonal interaction. This structural imbalance highlights a critical empathy gap where learners successfully acquire theoretical knowledge about cyberbullying but lack the pedagogical and dialogic support needed to internalise socio-emotional skills for sustainable behavioural change. Significance:this study proposes a strategic framework for integrating the gamified mobile learning into primary school curriculum to address these limitations. The findings contribute to the advancement of the educational body of knowledge by highlighting the importance of mobile-mediated, game-based interventions in equipping young learners with the competencies that required to navigate and respond to cyberbullying.